Application of design thinking for Quranic exegesis - Aliti, Ramadan (Penerbit Universiti Kebangsaan Malaysia, 2021)
The challenges of modern times, the fragmentation of knowledge on one hand, and the need for sustainable global solutions on the other hand, also require the contextualization of the Divine Message. This manuscript tends to offer alternative approaches to Quranic interpretation through the application of Design Thinking (DT) methodology. This approach maintains Quranic coherence, but it also restructures and systematizes man's relationship with the divine book. DT ensures the comprehensiveness and continuity of the methods and techniques of Quranic interpretation to date, making the Quran an essential factor in providing solutions to global challenges.